Calibration of UV-sensitive camera for corona detection - Du Toit, Nicolaas Serdyn (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.